2022
DOI: 10.1111/bcpt.13708
|View full text |Cite
|
Sign up to set email alerts
|

SmartPAN: In vitro and in vivo proof‐of‐safety assessments for an intra‐operative predictive indicator of postoperative pancreatic fistula

Abstract: Pancreatic surgery is complicated by untreated fluid leakage, but no tenable techniques exist to detect and close leakage sites during surgery. A novel hydrogel called SmartPAN has been developed to meet this need and is here assessed for safety before trials on human patients. First, resazurin assays were used to test the cytotoxic effects of SmartPAN's active bromothymol blue (BTB) indicator and its solution of phosphate‐buffered saline (PBS) on normal (HPDE: human pancreatic duct epithelial) or carcinomic (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 49 publications
(106 reference statements)
0
6
0
Order By: Relevance
“…Degradable starch microspheres are routinely used as haemostatic (Arista by BD, NJ, USA) and embolic agents (EmboCept S by PharmaCept, Berlin, Germany or EmboLog S by Serumwerk Bernburg, Germany). Pharmacokinetic measurements demonstrated that BTB was not detectable in abdominal drainage 2 days after surgery and it could not be detected in the bloodstream 27. Overall, the components of SmartPAN are either biocompatible or quickly neutralised by dilution and drainage.…”
Section: Ethics and Disseminationmentioning
confidence: 96%
See 3 more Smart Citations
“…Degradable starch microspheres are routinely used as haemostatic (Arista by BD, NJ, USA) and embolic agents (EmboCept S by PharmaCept, Berlin, Germany or EmboLog S by Serumwerk Bernburg, Germany). Pharmacokinetic measurements demonstrated that BTB was not detectable in abdominal drainage 2 days after surgery and it could not be detected in the bloodstream 27. Overall, the components of SmartPAN are either biocompatible or quickly neutralised by dilution and drainage.…”
Section: Ethics and Disseminationmentioning
confidence: 96%
“…Pharmacokinetic measurements demonstrated that BTB was not detectable in abdominal drainage 2 days after surgery and it could not be detected in the bloodstream. 27 Overall, the components of SmartPAN are either biocompatible or quickly neutralised by dilution and drainage. Usage of SmartPAN in this study is fully aligned to its field of application according to CE-approved market-registration.…”
Section: Ethics and Disseminationmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of somatostatin analogues also failed to significantly reduce the rate of POPF development 18 19. The recently developed intraoperative pancreatic leakage indicator ‘SmartPAN’, a device for the immediate detection of pancreatic leakages, is currently being investigated 20…”
Section: Introductionmentioning
confidence: 99%